Numerical Investigation of the Effect of Variable Baffle Spacing on the Thermal Performance of a Shell and Tube Heat Exchanger - Halil Bayram; Gökhan Sevilgen (Energies, 2017)
In this present study, numerical and theoretical analysis were both used to investigate the effect of the variable baffle spacing on the thermal characteristics of a small shell and tube heat exchanger. The numerical study was performed by using a three dimensional computational fluid dynamics (CFD) method and the computations were performed under steady-state conditions. We employed five different cases where the first had equal baffle spacing and the others had variable ones considering different configurations for balancing the pressure drop on the shell side. Theoretical calculations were run using the Bell-Delaware and Kern methods which are the most commonly used methods in the available literature. We show that the thermal performance of a shell and tube heat exchanger can be improved by evaluating together the results of the CFD and Bell-Delaware methods. From the numerical results, we can say that variable spacing with centered baffle spacing scheme can be proposed as an alternative shell side construction layout compared to an equal baffle spacing scheme. The numerical results were in good agreement with the theoretical data in the available literature.